PERANAN SOMASI SEBAGAI UPAYA HUKUM PENANGANAN PERKARA TENDER - Daniel Fransisco Rossi; Martono Anggusti (ADISAM PUBLISHER, 2025)
A summons is a legal tool used to provide official notification to a party suspected of violating provisions or agreements, before taking further legal action. In the context of a dispute, a summons serves as an attempt at peaceful resolution, giving the parties involved the opportunity to correct mistakes without going through the court process. In addition, a summons creates evidence of good faith in resolving a dispute, and can be a legal basis if the case continues to litigation. Through a summons, the injured party can increase legal awareness and encourage more constructive negotiations, which are expected to reduce conflict and facilitate a more efficient resolution. The main function of a subpoena is as a means of negotiation and settlement outside of court, which aims to prevent conflict escalation and accelerate peaceful resolution